ANALISIS DURASI PEMBAYARAN MANFAAT PENSIUN BERKALA PADA PROGRAM JAMINAN SOSIAL PENSIUN DI INDONESIA MENGGUNAKAN METODE COX PROPORTIONAL HAZARD - Alfi Faridatus Saadah; Tyogo Purwono (Jurnal Gaussian, 2022)
Uncertainty of the expiration date of payment defined benefit pension to Pension Social Security participants, makes the company has to work hard to ensure adequacy of fund to pay pension benefits in the long term. To test about pattern of the duration of payment defined benefit pension and the factors that affect can use the cox proportional hazard method. Through the cox proportional hazard method, it can be seen the relationship between the factors that cause an event to occur (time-dependent covariate) and the response variable is survival time.  The results of the analysis using the nonparametric survival method indicate that the probability for the time duration of payment defined benefit pension changes significantly in a period of less than 10 months is still relatively high. Using the forward selection method with Cox proportional hazard model, we obtained information that the recipient relationship, age, contribution period, and working capital protection risk rate are the factors that make the best-fit model with the smallest -2 log likelihood ratio, which is 216400.77.